1999
DOI: 10.1103/physrevb.60.14265
|View full text |Cite
|
Sign up to set email alerts
|

Electron escape from InAs quantum dots

Abstract: We identify fundamental mechanisms of electron escape from self-organized InAs quantum dots ͑QD's͒ in a vertical electric field by time-resolved capacitance spectroscopy. Direct tunneling and a thermally activated escape process are observed. The QD electron ground and first-excited states are concluded to be located ϳ190 and ϳ96 meV below the GaAs matrix conduction band, respectively. Our experimental results and their interpretation are in good agreement with eight-band k•p calculations and demonstrate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
94
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 31 publications
28
94
2
2
Order By: Relevance
“…In this paper we report on a second, slow and temperature-independent emission component, observed in DLTS spectra of Co-and Cr-implanted Ge. Its spectral characteristics are similar to those of a parallel carrier emission path reported for quantum wells and dots in III-V semiconductors [12][13][14][15][16][17][18][19] that was assigned to direct, through barrier tunnelling. The hole emission component reported here is, however, much slower and only becomes apparent in the spectrum when recording transients with large observer window time (t W ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this paper we report on a second, slow and temperature-independent emission component, observed in DLTS spectra of Co-and Cr-implanted Ge. Its spectral characteristics are similar to those of a parallel carrier emission path reported for quantum wells and dots in III-V semiconductors [12][13][14][15][16][17][18][19] that was assigned to direct, through barrier tunnelling. The hole emission component reported here is, however, much slower and only becomes apparent in the spectrum when recording transients with large observer window time (t W ).…”
Section: Introductionsupporting
confidence: 75%
“…In the DLTS spectra of certain quantum wells and dots a similar low-temperature non-thermal emission component has been observed and explained as the result of direct tunneling of a carrier out of the quantum well. [12][13][14][15][16][17][18][19] Other tunneling mechanisms that have been proposed for carriers out of defects or quantum wells, in particular phonon-and thermally assisted tunneling, are essentially thermally activated processes and cannot explain the current observations. In the case of direct tunneling, a strong dependence of τ c on electric field is expected, as the field determines the width of the tunnel barrier and it may in addition lower the barrier height for attractive centers (Poole-Frenkel effect).…”
Section: Origin Of the Non-thermal Emissionmentioning
confidence: 70%
“…Thermal carrier escape is proportional to exp (-E A /kT), where k is the Boltzmann constant, T the temperature in Kelvin and E A is the activation energy of this process. The highest activation energies found in the literature for the InAs/GaAs system vary between 94 and 115 eV [12][13][14]. In [12] an activation energy of 224 meV was measured for sample SB, in which dots were capped with a specifically designed InAlGaAs QD capping layer [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, impurities located at the epilayer/substrate interface have often been reported to degrade the expected performance of GaAs heterostructure devices. 3,4 Studies to determine the nature of these interfacial impurities have been conducted using a range of techniques including photoreflectance spectroscopy, 5,6 capacitanceversus-voltage measurements, 7 deep-level transient spectroscopy, 8 and secondary ion mass spectroscopy. 9,10 According to these studies, it has been shown that the presence of interfacial carbon impurities shifts the threshold voltage of field-effect transistors due to changes in band structure, 3 which reduces the electron mobility and density in the channel as the thickness of the buffer layer between the substrate and active channel decreases.…”
Section: Off-axis Electron Holographic Potential Mapping Across Algaamentioning
confidence: 99%